PERAN KOMUNIKASI DALAM BUDAYA ORGANISASI DALAM FENOMENA KISRUH PARTAI DEMOKRAT - Leti Karmila; Adli (Jurnal Ilmu Komunikasi Balayudha, 2021)
There are two characteristics of organizational culture, namely the characteristics of a strong organizational culture and the characteristics of a weak organizational culture. Strong organizational culture is a culture where the core values ​​of the organization are held intensively and widely shared by members of the organization. Meanwhile, if these values ​​are ignored or violated, it means that the organizational culture is weak. The disputes that occurred between various factions within the Democratic Party so as to destabilize the existence of the party showed the weak organizational culture of the party. As the ruling party, the Democratic Party has a duty to improve the welfare of all the people, not just being busy taking care of the party itself. However, the cases that hit this party make it quite difficult for the party to fix the party as well as lead it. This condition makes it more difficult for the party to build the image of the party to win the 2014 election.